Membaca Lukisan I Wayan Arnata melalui Kajian Semiotik Charles Sanders Peirce - Ni Wayan Satiani Pradnya Paramita (Mahesa Research Center, 2022)
This article examines the paintings by I Wayan Arnata, a Balinese artist. I Wayan Arnata consistently explores spiritual themes, exploring the philosophy of life as embodied in the traditional ngJdi decoration technique. The purpose of this study is to examine the symbolic meaning of the work based on the semiotic theory of C.S. Peirce using qualitative descriptive research methods. Data were obtained through interviews with key informants: I Wayan Arnata (48 years old) and triangulated analysis with I Wayan Arnata's documents. The results of this study describe the nature of art for I Wayan Arnata and the concept of understanding Hindu-Balinese philosophy. The concept of the Tri Hita Karana philosophy, as the basis for understanding the creative process of harmony between humans and others, humans and the environment, and intrapersonal relationships with God. In his works, these spiritual values find a new space in I Wayan Arnata's interpretation of the expression of spiritual values expressed through visual language through formalistic aspects.